(untitled) (Eurasian Medical Research Periodical, 2023)
The article describes the main pathophysiological mechanisms underlying the potential use of antirheumatic therapy in the new COVID-19 in patients with rheumatic diseases. Also, it summarizes current data on the risk and outcome of COVID-19 in patients with systemic autoimmune diseases. To date, there are no large randomized studies on the use of antirheumatic drugs in patients with rheumatic diseases in the setting of COVID-19. Besides, there is no convincing evidence that any disease-modifying antirheumatic drug (conventional synthetic, biological, or targeted synthetic) can prevent the development of a severe COVID-19 course. At the same time, the importance of concomitant pathology (hypertension, obesity, cardiovascular diseases, diabetes mellitus) and risk factors (smoking) in the development of a severe COVID-19 course in patients with rheumatic diseases is shown. The article presents possible options for initiating and continuing treatment with antirheumatic drugs in pa tients with rheumatic diseases, depending on the stage of the infectious disease process